Model for Insurance Fraud Risk Assessment and Prevention (UNWE Yearbook, 2017)
This article critically examines insurance frauds in terms of the risk they create and the significant losses they bring to the insurance industry. A comparative analysis of the classification of insurance frauds in the legal systems of many developed countries has been conducted. A model for risk assessment and the prevention of insurance frauds is presented. In the suggested model the overall risk assessment is achieved by the evaluation of risk elements – probability, exposure (frequency) and results. The possibilities for the practical application of the model of insurance frauds assessment and prevention in the insurance organizations practices have been outlined.